2013
DOI: 10.1590/s0100-736x2013000900008
|View full text |Cite
|
Sign up to set email alerts
|

Produção e purificação de imunoglobulinas Y policlonais anti-Leptospira spp.

Abstract: Objetivou-se verificar se galinhas imunizadas com uma solução de Leptospira interrogans inativadas e proteínas de membrana externa do sorovar Hardjo, poderiam produzir anticorpos policlonais específicos anti-leptospiras, detectáveis em testes ELISA. Foram imunizados oito galinhas com 25 semanas de idade, da raça White Leghorn, sendo três imunizadas com uma suspensão de leptospiras inativadas, três com uma solução de proteínas de membrana externa extraída do sorovar Hardjo e duas controle. Coletas de sangue for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
1
0
1
Order By: Relevance
“…This study demonstrated that hens immunized with strain B19 produced IgY antibodies reactive to this antigen, which were detectable by indirect ELISA and by official tests for the diagnosis of bovine brucellosis, BAPA and 2-ME, representing a good choice for the production the polyclonal antibodies, like showed in study with the production of high titers of specific polyclonal IgY antibodies to Leptospira [24].…”
Section: Discussionmentioning
confidence: 54%
“…This study demonstrated that hens immunized with strain B19 produced IgY antibodies reactive to this antigen, which were detectable by indirect ELISA and by official tests for the diagnosis of bovine brucellosis, BAPA and 2-ME, representing a good choice for the production the polyclonal antibodies, like showed in study with the production of high titers of specific polyclonal IgY antibodies to Leptospira [24].…”
Section: Discussionmentioning
confidence: 54%
“…Anticorpos específicos, policlonais ou monoclonais, para diagnóstico, pesquisa e terapias tem sido obtido especialmente de mamíferos tais como coelhos e ratos (Tavares et al, 2013). Batista et al (2019) os anticorpos são ferramentas biotecnológicas de alto valor, representando o segmento de maior crescimento no mercado de produtos biológicos alcançando atualmente.…”
Section: Resultsunclassified